A modified two-stage isolated bidirectional buck-DAB converter with a full-load ZVS range - Li, Jinliang; Wan, Dai; Lu, Zhengmei; Xu, Guo (Frontiers in Energy Research, 2024)
A modified two-stage buck-DAB (MBDAB) converter is proposed to improve the performance of the traditional two-stage buck-DAB (TSBDAB) converter. In the MBDAB converter, the DAB can work with fixed voltage gain and voltage-matched condition under a wide input voltage range. The voltage gain of the converter is adjusted through the added front-end stage, which is similar to a buck converter. Compared with the TSBDAB converter, only part of the transmitted power flows through the front-end stage, so the loss of the buck stage and the burden of zero-voltage switching (ZVS) can be reduced. Detailed analysis of the working principle, partial power characteristics, and the full-load ZVS range design are presented. To verify the effectiveness of the proposed MBDAB converter, experimental results are obtained from a prototype with a rated power of 1 kW.